Enterohepatic cycling of bilirubin as a cause of 'black' pigment gallstones in adult life - Vítek, L; Carey, M C (European journal of clinical investigation, 2003)
In contrast to bile salts, which undergo a highly efficient enterohepatic circulation with multiple regulatory and physiologic functions, glucuronic acid conjugates of bilirubin are biliary excretory molecules that in health do not have a continuing biologic life. Intestinal absorptive cells are devoid of recapture transporters for bilirubin conjugates, and their large size and polarity prevent absorption by passive diffusion. However, unconjugated bilirubin, the beta-glucuronidase hydrolysis product of bilirubin glucuronides can be absorbed passively from any part of the small and large intestines. This can occur only if unconjugated bilirubin is kept in solution and does not undergo rapid bacterial reduction to form urobilinoids. Here we collect, and in some cases reinterpret, experimental and clinical evidence to show that in addition to the well-known occurrence in newborns, enterohepatic cycling of unconjugated bilirubin can reappear in adult life. This happens as a result of several common conditions, particularly associated with bile salt leakage from the small intestine, the most notable ileal dysfunction resulting from any medical or surgical cause. We propose that when present in excess, colonic bile salts solubilize unconjugated bilirubin, delay urobilinoid formation, prevent calcium complexing of unconjugated bilirubin and promote passive absorption of unconjugated bilirubin from the large intestine. Following uptake, reconjugation, and resecretion into bile, this source of 'hyperbilirubinbilia' may be the important pathophysiological risk factor for 'black' pigment gallstone formation in predisposed adult humans.
Keywords: Liver; játra; Cholelithiasis; dieta; Pigments, Biological; biologické pigmenty; Crohnova nemoc; Adult; Intestinal Mucosa; žlučové kyseliny a soli; Malabsorption Syndromes; Cystic Fibrosis; Enterohepatic Circulation; Humans; Bile Acids and Salts; Bilirubin; malabsorpční syndromy; střevní sliznice; Crohn Disease; bilirubin; Diet; Solubility; cholelitiáza; dospělí; rozpustnost; lidé; cystická fibróza; enterohepatická cirkulace